Toxin-neutralizing antibodies protect against Clostridium perfringens-induced necrosis in an intestinal loop model for bovine necrohemorrhagic enteritis - Goossens, Evy (BMC Vet Res, 2016)
BACKGROUND: Bovine necrohemorrhagic enteritis is caused by Clostridium perfringens type A. Due to the rapid progress and fatal outcome of the disease, vaccination would be of high value. In this study, C. perfringens toxins, either as native toxins or after formaldehyde inactivation, were evaluated as possible vaccine antigens. We determined whether antisera raised in calves against these toxins were able to protect against C. perfringens challenge in an intestinal loop model for bovine necrohemorrhagic enteritis. RESULTS: Alpha toxin and perfringolysin O were identified as the most immunogenic proteins in the vaccine preparations. All vaccines evoked a high antibody response against the causative toxins, alpha toxin and perfringolysin O, as detected by ELISA. All antibodies were able to inhibit the activity of alpha toxin and perfringolysin O in vitro. However, the antibodies raised against the native toxins were more inhibitory to the C. perfringens-induced cytotoxicity (as tested on bovine endothelial cells) and only these antibodies protected against C. perfringens challenge in the intestinal loop model. CONCLUSION: Although immunization of calves with both native and formaldehyde inactivated toxins resulted in high antibody titers against alpha toxin and perfringolysin O, only antibodies raised against native toxins protect against C. perfringens challenge in an intestinal loop model for bovine necrohemorrhagic enteritis.